Is there long-term value of pathology scoring in immunoglobulin A nephropathy? A validation study of the Oxford Classification for IgA Nephropathy (VALIGA) update. Issue 6 (9th November 2018) - Coppo, Rosanna; D'Arrigo, Graziella; Tripepi, Giovanni; Russo, Maria Luisa; Roberts, Ian S D; Bellur, Shubha; Cattran, Daniel; Cook, Terence H; Feehally, John; Tesar, Vladimir; Maixnerova, Dita; Peruzzi, Licia; et al.
Abstract: Background: It is unknown whether renal pathology lesions in immunoglobulin A nephropathy (IgAN) correlate with renal outcomes over decades of follow-up. Methods: In 1130 patients of the original Validation Study of the Oxford Classification for IgA Nephropathy (VALIGA) cohort, we studied the relationship between the MEST score (mesangial hypercellularity, M; endocapillary hypercellularity, E; segmental glomerulosclerosis, S; tubular atrophy/interstitial fibrosis, T), crescents (C) and other histological lesions with both a combined renal endpoint [50% estimated glomerular filtration rate (eGFR) loss or kidney failure] and the rate of eGFR decline over a follow-up period extending to 35 years [median 7 years (interquartile range 4.1–10.8)]. Results: In this extended analysis, M1, S1 and T1–T2 lesions as well as the whole MEST score were independently related with the combined endpoint (P < 0.01), and there was no effect modification by age for these associations, suggesting that they may be valid in children and in adults as well. Only T lesions were associated with the rate of eGFR loss in the whole cohort, whereas C showed this association only in patients not treated with immunosuppression. In separate prognostic analyses, the whole set of pathology lesions provided a gain in discrimination power over the clinical variables alone, which was similar at 5 years (+2.0%) and for the whole follow-up (+1.8%). A similar benefit was observed for risk reclassification analyses (+2.7% and +2.4%). Conclusion: Long-term follow-up analyses of the VALIGA cohort showed that the independent relationship between kidney biopsy findings and the risk of progression towards kidney failure in IgAN remains unchanged across all age groups and decades after the renal biopsy.